Penerapan Metode Sorogan Berbasis Peta Konsep dalam Pembelajaran Kitab Nahwu Al-Jurumiyah di Pondok Pesantren An-Nur Kota Probolinggo - Roni Ahmad Syaifudin; Abdulloh Shodiq (Almustofa Journal of Islamic Studies and Research, 2026)
Learning classical Islamic texts (kitab kuning) is one of the distinctive characteristics of Islamic boarding school education, aiming to develop students' ability to understand Arabic Islamic literature. One of the primary books used in learning Arabic grammar is Al-Jurumiyah. However, many students still experience difficulties in understanding grammatical rules and reading unvowelled Arabic texts. This study aims to describe the implementation of the concept map-based sorogan method in learning Al-Jurumiyah, explain its implementation process, and analyze its impact on students’ understanding at An-Nur Islamic Boarding School, Probolinggo. This research employed a qualitative descriptive approach. Data were collected through participant observation, in-depth interviews, and documentation. Data analysis included data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the concept map-based sorogan method was implemented systematically through preparation, implementation, evaluation, and follow-up stages. Concept maps assisted students in understanding relationships among grammatical concepts, making learning more meaningful. The implementation of this method improved students’ ability to read classical Arabic texts, understand grammatical rules, enhance self-confidence, discipline, and classroom participation. Therefore, integrating the sorogan method with concept maps represents an effective instructional innovation for